Determination and Comparison of the Extractives Chemical Compounds in Wood and Bark of Planted Eldar Pine Tree by GC-MS Methods - Vaysi, Ramin; Sajad Ashrafi, S. (Asian Journal of Chemistry, 2012)
Eldar pine tree is one of the species that planted in city parks, garden and forests region of Tehran and another city of Iran. In this study, three trees from species of planted elder pine tree were randomly cut down in planted forest region of Tehran city. Then from each tree were separated three disks. At first wood flour and then extractive measured by TAPPI standards. The results showed that the average of extractives in wood and bark of planted elder pine tree were 3.6 and 17 %, respectively. Then wood flour was washed by acetone and extractives residue was added BSTFA reactor and samples kept in Ben Marry Bath in 70 ºC for 1 h and were analyzed by GC/MS. For the identification of compounds were used GC diagram which shows abundance and retention time of each compound, and calculation of quartz index and Adams table. So that, specified 56 compounds in wood and 43 compounds were in bark of planted elder pine tree. That 1-phenanthrenecarboxylic acid, rosin acids, g-sitosterol, 9-octadecanoic acid, n-hexadecanoic acid, octadecanoic acid, 9,12-octadecanoic acid, dodecan, tetradecan, styrene and hexadecan were as 11 common compounds in wood and bark of planted elder pine tree so much and these compounds are very important in durability and its consumption.